2019
DOI: 10.5812/aapm.92929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flexible Laryngeal Mask Airway® in Tongue Trauma Repair: A Randomized Trial

Abstract: BackgroundFlexible laryngeal mask airway may be used instead of the endotracheal tube in children presented for elective repair of tongue trauma, as it may shorten the time for extubation and recovery with the amelioration of stress response to airway management.ObjectivesThis study aimed to evaluate the extubation time and hemodynamic response to the endotracheal tube or flexible laryngeal mask airway in children presented for tongue trauma repair.MethodsThe study recruited 90 children presented for elective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In terms of difficult airway management, the upper airway nerve block method may be proper for tracheal stenosis patients who are rigid bronchoscopy candidates (63). Also, it is suggested that video laryngoscopy in comparison to direct laryngoscopy can provide better visualiza-tion for intubation of the trachea in congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of difficult airway management, the upper airway nerve block method may be proper for tracheal stenosis patients who are rigid bronchoscopy candidates (63). Also, it is suggested that video laryngoscopy in comparison to direct laryngoscopy can provide better visualiza-tion for intubation of the trachea in congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Mohamed in 90 Egyptian children involving oral surgeries, such as tonsillectomy in whic h laryngeal masks were used, reported minor complication compared to those receiving an endotracheal tube in which nausea 8.89%, cough 6.67%, laryngospasm 2.22%, odynophagia 4.44% were found. Extubation and recovery times were significantly shorter with the mask thus indicating that the laryngeal mask is safe in airway surgeries [4].…”
Section: Discussionmentioning
confidence: 90%
“…In a 2013 meta-analysis, Barreira analyzed 29 prospective and randomized clinical trials and showed that patients undergoing general anesthesia with the use of the laryngeal mask have fewer opportunities to develop complications, such as hoarseness, cough, and laryngospasm [3]. In addition, extubation and recovery times and hemodynamic responses were significantly shorter compared to those of the endotracheal tube [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if the patient is nil per os (NPO), the classical LMA can be an appropriate solution (16,17). Furthermore, in short surgeries, the use of classical LMA with narcotics, midazolam, and propofol without muscle relaxants and with the help of inhaled gasses allows reducing the complications of anesthesia and recovery time at the end of the operation (18,19).…”
Section: Introductionmentioning
confidence: 99%